Dose sensitivity of MAGIC-f polymer gel using different MRI sequences - Nícollas Gonçalves Cavedini; Ricardo Meurer Papaléo; Nícolas Borges Jobim; Phelipi Nunes Schuck; Fabrício Nery Garrafiel; Elisa Magno Nunes de Oliveira; Marcelo Menna Barreto Schwarcke; Alex Cristóvão Holanda de Oliveira; Paulo Rauli Rafeson Vasconcelos Caribé; Ana Maria Marques da Silva (Brazilian Journal of Radiation Sciences)
This study aims to evaluate the dose sensitivity of MAGIC-f  gel irradiated by high-energy photon beams, comparing quantification using different MRI sequences. Irradiation was performed using 6 MV photons with 600 cGy/min dose rate, field size of 20x20 cm², and 94 cm source-to-surface distance. Two gel batches were produced on different days and placed in vials. In the first batch, doses of 0, 2, 4, 6, 8, 10, 20, and 40 Gy were planned. The second batch was irradiated with doses of 0, 2, 4, 6, 10, 12, 14, and 16 Gy. MR images were acquired with Spin Echo (SE, TR=3 s) and Multi Spin Echo (MSE, TR = 3s or 10s, turbo factor 24) sequences. The dose is assessed via changes in the transverse relaxation time in the irradiated gel. In MSE, dose sensitivity in the first batch was 0.27 (TR=3 s) and 0.28 Gy-1s-1  (TR=10 s) and in the second batch, 0.31 and 0.31 Gy-1s-1 (TR = 3 s and TR = 10 s, respectively). In the SE sequence, dose sensitivity was 0.42 for the first batch and 0.43 Gy-1s-1 for the second batch. Linearity of dose-response was only obtained for doses below 10 Gy. Comparing the dose sensitivity extracted from MSE and SE sequences using TR= 3s, differences around 30% were found. Thus, although MSE-MRI offers a faster protocol of imaging acquisition it is less precise for quantification of relaxation times, as TE is not a well-defined quantity. The performance of the gel as a dosimeter is consequently sequence dependent.